Pengembangan Model Pertanian Berkelanjutan Melalui Integrasi Teknologi Akuaponik dan Budidaya Nila - Anisa; Hikmah Marisda, Dewi (Pusat Pengembangan Pendidikan dan Bakat Indonesia/Education and Talent Development Center of Indonesia (ETDC Indonesia), 2026)
This community service activity was motivated by the still simple management of vegetable cultivation at MTs Hizbul Wathan Belapuranga, even though the partners already have potential in the form of tilapia cultivation ponds, school land, and student entrepreneurship activities. The previous vegetable cultivation had not been integrated with efficient agricultural technology so that production results were not optimal. This activity aims to develop a sustainable agricultural model through the integration of tilapia and vegetable cultivation with an aquaponics system and to improve the knowledge and skills of partners in school-based integrated cultivation management. The implementation method of the activity was carried out in a participatory manner through the stages of preparation, field observation, system design, installation, counseling, training, mentoring, and monitoring and evaluation. The target of the activity included groups of teachers and students involved in the management of school business units. The activity focused on introducing the aquaponics system, vegetable cultivation techniques, tilapia maintenance, and strengthening the management of simple school-based businesses. The results of the activity showed that 1 aquaponic installation unit had been built in the school environment with the type of vegetable cultivated being lettuce. The results of the activity showed that the aquaponic system could be a means of production, education, and strengthening school business units in a sustainable manner. This activity demonstrates that integrating tilapia and vegetable cultivation through an aquaponics system can be implemented as a model for school-based sustainable agriculture. The active involvement of teachers and students is a crucial element in strengthening the activity's success and opening up opportunities for developing more independent and sustainable school businesses. Keywords: aquaponics, tilapia cultivation, sustainable agriculture, school entrepreneurship